Hyperbaric oxygen therapy as adjuvant therapy for odontogenic necrotizing myositis: A case report. Issue 9 (30th August 2021) - Cracchiolo, Andrea N.; Palma, Daniela Maria; Palmeri, Marco; Tantillo, Diego; Lo Bue, Rosalia; Braconi, Andrea; Caramanna, Claudio; Solazzo, Luigi; Genco, Fabio; Mirto, Paola
Abstract: In a young man affected by skin soft tissue infections complicated with myositis, the use of hyperbaric oxygen treatment as an adjuvant therapy to surgical debridement and antibiotic therapy could improve management and prognosis. Abstract : In a young man affected by skin soft tissue infections complicated with myositis, the use of hyperbaric oxygen treatment as an adjuvant therapy to surgical debridement and antibiotic therapy could improve management and prognosis.